Factoring research and pastoralists in the One Health framework in Ethiopia - Flintan, Fiona E. (International Livestock Research Institute, 2025)
A presentation on rangeland health and rangeland health workers was presented at the Global Alliance of Sustainable Livestock webinar on Innovating Governance for Sustainable Rangelands and Pastoralist Livelihoods, December 2025.